A Homicide Mimicking Accidental Death - Salaçin, Serpil; Çekin, Necmi; Gülmen, Mete Korkut; Şen, Fatih; Özdemir, Mehmet Hakan (The Bulletin of Legal Medicine, 1996)
A medicolegal investigation consists of adequate information about the past, crime scene investigation and performing an autopsy with laboratory analysis. The cause of death is based on a careful review of all the available information. When subsequent information leads to an alteration of an opinion without performing an autopsy, the cause of death and the death certificate may need to be revised. In this paper, the crime scene investigation of a body who was found near by a building construction was revieweci. Traumatic head injury was found and an accidental death had been described by the eyewitnesses. The autopsy revealed shotgun injuries and the case was discussed by the means of medicolegal importance. Key words: Shotgun Wounds, Cause of Death, Medicolegal Investigation, Crime Scene, Autopsy.
Keywords: Shotgun Wounds; Cause of Death; Medicolegal Investigation; Crime Scene; Autopsy